The economic burden associated with skeletal-related events in patients with bone metastases secondary to solid tumors in Belgium. Issue 4 (April 2013) - Body, Jean-Jacques; Chevalier, Pierre; Gunther, Oliver; Hechmati, Guy; Lamotte, Mark
Abstract Objectives: More than 1.5 million patients worldwide are affected by bone metastases. Patients with bone metastases frequently develop skeletal-related events (SREs, including radiation to bone, non-vertebral fracture, vertebral fracture, surgery to bone, and spinal cord compression) that are associated with high healthcare costs. This study aims to provide an estimate of the cost per SRE in both the inpatient and outpatient settings in Belgian patients with bone metastases secondary to solid tumors (breast, prostate, and lung cancers). Methods: Patients were retrieved from the IMS Hospital Disease database from 2005–2007. Inclusion was based on the International Classification of Diseases and Related Health Problems Version 9 (ICD-9) diagnosis and/or procedure codes covering patients with breast, prostate, or lung cancer with bone metastases who were hospitalized for one or more SREs. All costs were extrapolated to 2010 using progression in hospitalization costs since 2001. Additional outpatient costs resulting from radiation to bone and diagnostic tests performed in ambulatory settings were estimated by combining published unit costs with resource use data obtained from a Delphi panel. Results: The average cost per SRE across solid tumor types based on the weighted average of inpatient and outpatient costs was €2653 for radiation to bone, €5015 for a vertebral fracture, and €7087 for a non-vertebral fracture. Costs were €12, 885 and €15, 267 for surgery to bone and spinal cord compression, respectively. Limitations: No patient follow-up across calendar years could be done. Also, details regarding the exact anatomic sites of SREs were not always available. Conclusions: SREs add a substantial cost to the management of patients with bone metastases. Avoiding SREs can lead to important cost-savings for the healthcare payer.